Tutorial On The designing Learning Devices For Preschool Teachers at Kindergarten Aisyiyah 2 Palu - Nurhayati, Nurhayati; Awalunisah, Sita; Imamah, Zakiyyatul (Institute of Education and Social Research, 2024)
Learning tools in Early Childhood Educatioan are a system that aims to enable teachers to understand what is planned in concept planning based on the curriculum that applies to Early Childhood Education. Teachers need to have the competence to design learning for Early Childhood based on play and game theory in order to realize learning that is in accordance with the characteristics of 21st century children, design learning that is innovative, creative and in line with the child's level of development and the demands of science and technology development, implement learning for early childhood that is in accordance with the demands of 21st century developments. This competency will create good learning and be implemented systematically and continuously. The main aim of this service is to increase the competency of Early Childhood Education teachers in creating learning device.